GRUING STUDIeS IN THE ARID AND SEMI-ARID ZONES OF RAJAStHAN V. Assessment of forage resources of afforested and stablised dunes in tbe initial year of utilization - Chakravaty, A K; Bhati, G N (Annals of Arid Zone, 2016)
Grazing study with heifers was conducted in 45 hectares of protected and afforested sand dunes for a period of 263 days. The average utilization of forage was 66.5 per cent. Brachiaria ramosa. Digitaria marginata. Panicum antidotale were grazed compeletely. whereas Crotalaria burhia, Cmbopogon sp. and Boerhavia diffusa remained almost unutilised. There was no significant decrease in total plant cover due to the short period of grazing